Stable Isotopes (δ13C, δ15N) Combined with Conventional Dietary Approaches Reveal Plasticity in Central-Place Foraging Behavior of Little Penguins Eudyptula minor - Chiaradia, André; Ramírez, Francisco; Forero, Manuela G.; Hobson, Keith A. (Frontiers in Ecology and Evolution, 2016)
Marine top and meso predators like seabirds are limited by the need to breed on land but forage on limited or patchily distributed resources at sea. Constraints imposed by such central-place foraging behaviour change during breeding or even disappear outside the breeding period when there is no immediate pressure to return to a central place. However, central place foraging is usually factored as an unchanging condition in life history studies. Here we used little penguin Eudyptula minor, a resident bird with one of the smallest foraging range among seabirds, to examine the different degree of pressure/constraints of being a central-place forager. We combined data on isotopic composition (δ13C and δ15N), conventional stomach contents and body mass of little penguins breeding at Phillip Island, Australia over nine years (2003-11). We explored relationships between diet and body mass in each stage of the breeding season (pre-laying, incubation, guard, and post-guard) in years of “high” and “low” reproductive success. Values of δ13C and δ15N as well as isotopic niche width had similar patterns among years, with less variability later in the season when little penguins shorten their foraging range at the expected peak of their central-place foraging limitation. Body mass peaked before laying and hatching in preparation for the energetically demanding periods of egg production and chick provisioning. An increase of anchovy and barracouta in the diet, two major prey for little penguins, occurred at the critical stage of chick rearing. These intra-annual trends could be a response to imposed foraging constraints as reproduction progresses, while inter-annual trends could reflect their ability to match or mismatch the high energy demanding chick rearing period with the peak in availability of high-quality prey such as anchovy. Our findings underline the key advantages of using a stable isotope approach combined with conventional dietary reconstruction to reveal an otherwise intractable ecological issue of different constrains of being a central-place forager, such as the little penguin, which could be applied to other marine species.